Real Time Parallel Intraoperative Integration of Endoscopic, Microscopic, and Navigation Images: A Proof of Concept Based on Laboratory Dissections - Salma, Asem; Ammirati, Mario (Journal of Neurological Surgery Part B: Skull Base, 2012)
Endoscope, microscope, and neuronavigation systems are integrated in neurosurgical procedures mainly by using a serial combination algorithm, where, the user must switch his/her field of view from one platform display to another. The integration of theses devices could be optimized by incorporating different displays into one viewing platform thus achieving a parallel combination. In this study, we investigated the feasibility and the applicability of parallel integration of microscopic, endoscopic, and neuronavigation images by real time displaying the endoscope and neuronavigation image datasets in the main operative microscope oculars. The proposed set-up was effective in displaying the three images dataset in an operationally actionable mode. Ergonomically, the ability of using the different image dataset without the need of taking the eyes off the microscope oculars did not disrupt the flow or the tempo of the operative procedure. However, new endoscopes specific to this application are recommended.
Keywords: endoscope; image-guided surgery; microneurosurgery; medical technology; skull base surgery